PENGARUH KEBIASAAN BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN ADMINISTRASI PAJAK KELAS XI MELALUI MOTIVASI BELAJAR SISWA SMK NEGERI JAKARTA TIMUR - Delia Oktaviana, Vonny; Zulaihati, Sri; Sumiati, Ati (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2023)
This study aims to examine the effect of study habits on the learning outcomes of 11th-grade Tax Administration subjects among public vocational high school students in East Jakarta. The method used is a quantitative approach, employing proportional random sampling, resulting in a research sample of 122 students. Path analysis and hypothesis testing, including the T test, were utilized for data analysis. The study's findings reveal several significant relationships: there is a positive and significant influence between learning habits and learning outcomes, as well as between learning habits and learning motivation. However, no significant influence was found between learning motivation and learning outcomes, nor between learning habits and learning outcomes through learning motivation. These results indicate that higher levels of learning habits lead to better learning outcomes, and vice versa. Similarly, stronger study habits correlate with increased learning motivation, and vice versa. The research also reveals that student learning outcomes fall into the high category, while learning habits and learning motivation are in the medium category.